2022
DOI: 10.3390/buildings12020221
|View full text |Cite
|
Sign up to set email alerts
|

A gbXML Reconstruction Workflow and Tool Development to Improve the Geometric Interoperability between BIM and BEM

Abstract: The BIM-based building energy simulation plays an important role in sustainable design on the track of achieving the net-zero carbon building stock by 2050. However, the issues on BIM-BEM interoperability make the design process inefficient and less automatic. The insufficient semantic information may lead to results inaccurate while the error-prone geometry will terminate the simulation engine. Defective models and authoring tools lagging behind the standard often cause failures in creating a clean geometry t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Clashing between building elements (e.g., overlapping or unconnected walls or floors) is not usually accepted, only some of them do, with limited approach [32,33,38]. For solving the above, some works suggest the use of auxiliary third-party tools (such as Solibri [41]) to audit and fix the model for inconsistencies.…”
Section: Rationale Of the Research Beyond The State Of The Artmentioning
confidence: 99%
See 2 more Smart Citations
“…Clashing between building elements (e.g., overlapping or unconnected walls or floors) is not usually accepted, only some of them do, with limited approach [32,33,38]. For solving the above, some works suggest the use of auxiliary third-party tools (such as Solibri [41]) to audit and fix the model for inconsistencies.…”
Section: Rationale Of the Research Beyond The State Of The Artmentioning
confidence: 99%
“…For renovation and energy audit use-cases, these inputs are becoming more and more popular, and they usually produce BIM models which require cleaning and postprocessing for practical purposes. In some cases dependency of specific commercial tools is stated, either as authoring tool, or as an environment to implement the algorithm as a plugin, e.g., Autodesk Revit [32,33]. Multi-building approach is not targeted.…”
Section: Rationale Of the Research Beyond The State Of The Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The building energy simulation (BES) methodology enables a thermo-energetic performance analysis [3]. One way to conduct the process of data transfer within the BES software is to import an existing parameterized model; in other words, import a geometric model with building information associated with the elements [4].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the proposed workflow can improve the original model integrity and the energy simulation stability. Carvalho and Almeida [33] combined BIM and the Building Sustainability Assessment method (BSA) to improve the efficiency of building sustainability and used this approach to achieve the evaluation of the SBToolPT-H energy efficiency category. Pereira and Santos [34] made a systematic literature review to assess the current level of BIM adoption for building energy optimization.…”
mentioning
confidence: 99%